Enhancing the mechanical properties and providing bioactive potential for graphene oxide/montmorillonite hybrid dental resin composites - Velo, Marilia Mattar de Amôedo Campos; Filho, Francisco Gilmário Nunes; de Lima Nascimento, Tatiana Rita; Obeid, Alyssa Teixeira; Castellano, Lúcio Cançado; Costa, Reginaldo Mendonça; Brondino, Nair Cristina Margarido [UNESP]; Fonseca, Maria Gardennia; Silikas, Nikolaos; Mondelli, Rafael Francisco Lia (Springer Nature, 2022)
This in vitro study synthetized hybrid composite nanoparticles of graphene oxide (GO) and montmorillonite MMt (GO-MMt) by ultrasound treatments. Samples were characterized by X-ray diffraction, FT-Raman, FTIR, TEM and SEM. The effect of their incorporation (0.3% and 0.5%) on the mechanical properties in a resin-based composite (RBC) and their bioactivity potential were evaluated. The specimens were characterized by evaluating their 3-point flexural strength (n = 6), modulus of elasticity (n = 6), degree of conversion (n = 6), microhardness (n = 6), contact angle (n = 3) and SEM analysis (n = 3). In vitro test in SBF were conducted in the RBCs modified by the hybrid. Overall, the synthetized hybrid composite demonstrated that GO was intercalated with MMt, showing a more stable compound. ANOVA and Tukey test showed that RBC + 0.3% GO-MMt demonstrated superior values of flexural strength, followed by RBC + 0.5% GO-MMt (p < 0.05) and both materials showed higher values of microhardness. All groups presented a contact angle below 90°, characterizing hydrophilic materials. RBCs modified by the hybrid showed Ca and P deposition after 14 days in SBF. In conclusion, RBCs composed by the hybrid showed promising results in terms of mechanical properties and bioactive potential, extending the application of GO in dental materials.